Study of exercise treadmill test in type 2 diabetes mellitus patients - Nagrani, Sahil; Patil, Prajakta; Barsode, Supriya S.; Momale, Nisarg; Mehta, Parth (International Journal of Advances in Medicine, 2021)
Background: The aim of this study was to assess the prevalence and clinical predictors of silent myocardial ischemia in patients with type 2 diabetes mellitus, and the early diagnosis of coronary artery disease. Methods: A cross sectional prospective study was conducted including all confirmed diabetic patients in the age group between 40-60 in Bharati medical college hospital Pune in western Maharashtra. A detailed clinical examination and history was taken and relevant laboratory investigations, Electrocardiogram and Treadmill Stress test was done using Bruce protocol. The quantitative data was represented as their mean ± SD. Categorical and nominal data was expressed in percentage. All analysis was carried out by using SPSS software version 21. Results: Male preponderance was seen in the study with 64% of the study subjects. The mean age of the study subjects was 50.67±5.51 years. A p<0.001 was obtained showing positive correlation between BMI and TMT positivity. TMT positivity steadily increased with the duration of diabetes mellitus. Obtained p<0.001. The correlation between dyslipidemia and TMT positivity was significant, with a p=0.007. Correlation of Fasting as well as Post-prandial blood glucose levels with TMT positivity proved to be statistically significant, with a p<0.001. Conclusions: Exercise Treadmill test in diabetic patients has a significant role in screening diabetic individuals for coronary ischemia. The results obtained clearly indicate that an exercise treadmill test may be proposed as the first test for screening for coronary ischemia in diabetic population as it is safer, cheaper and non-invasive.